Expression of miR-141 and Osteogenic Gene Dlx5, Msx2 and Runx2 in Osteogenic Differentiation of BMSCs in Ovariectomized Osteoporosis Model Mice - Zhenpu WEI; Wenming ZHANG; Pan SUN; Zhiqiang WANG; Yanping LIN (康复学报)
Objective:To observe the expression difference and change trend of miR-141 and osteogenic gene Dlx5, Msx2 and Runx2 in osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) in the ovariectomy model group and the sham operation group, and investigate the mechanism of postmenopausal osteoporosis.Methods:Twenty 4-week-old clean C57 female mice were selected as the model group and the sham operation group according to the random number table method, and ten cases in each group. The mouse model of postmenopausal osteoporosis in the model group was established by ovariectomy, and the ovaries were preserved and only the fat around the ovaries were removed in the sham operation group. The mice in the model group were identified and successfully modeled two months after modeling, then BMSCs of mice in the two groups were isolated and cultured through whole marrow culture method. The morphology of the cells was observed and the cell phenotype was identified by flow cytometry. The osteogenic differentiation of BMSCs was observed by alkaline phosphatase staining, quantification and alizarin red staining on the 3rd, 8th and 13th day, respectively to observe the osteogenic ability of BMSCs. The expression of miR-141 and osteogenic genes Dlx5, Msx2 and Runx2 were detected by q-PCR on the 3 rd, 8th and 13th day after osteogenic induction of BMSCs. The protein expression of osteogenic gene was detected by Western blot.Results:Positive expression of CD29 and CD44 and negative expression of CD34 and CD45 in BMSCs were found by flow cytometry. After osteogenic induction of BMSCs in both groups, the expression of ALP gradually increased, reaching a peak on the 8th day, and then gradually decreased, showing a"∧"type change. The model group was lighter than the sham operation group, and the result of activity detection was consistent with the degree of staining. The expression of ALP in model group was lower than that of the sham operation group after osteogenic differentiation on the 3rd, 8th and 13th day (P< 0.05). When the two groups of cells were stained with alizarin red, calcified nodules appeared on the 8th day, and the number of calcified nodules increased on the 13th day. There was no significant difference in the number of calcified nodules between the model group and the sham operation group on the 3rd and 8th day of osteogenic induction. On the 13th day, compared with the sham operation group, the number of calcified nodules in the model group was less, and osteogenic differentiation slowed down significantly. On the 3rd, 8th and 13th day of osteogenic induction, the expression of Dlx5 and Runx2 were increased continuously, and miR-141 and Msx2 were decreased continuously (P< 0.05). Compared with the 3rd day, the indexes of the 8th day and the 13th day were significantly different (P< 0.05). Comparison of between groups showed that the expression of miR-141 and Msx2 in the model group was higher, and the expression of Dlx5 and Runx2 was lower than those in the sham operation group (P< 0.05).Conclusion:The ability of osteogenic differentiation in BMSCs is affected by ovariectomy. MiR-141 and Msx2 are negative regulators, and Dlx5 and Runx2 are positive regulators in osteogenic differentiation of BMSCs.